Stabilitas Ekonomi Makro Indonesia Menghadapi Resesi Global Akibat Perang Rusia-Ukraina Pada Tahun 2022 - Wijaya, Muhammad Ar Raafi Caisar; Iqbal, Muhammad; Albayumi, Fuat (University of Jember, 2024)
Indonesia is a country whose economy is quite stable in the midst of a global recession. Indonesia recorded economic growth amidst the pressure of a global recession due to the Russia-Ukraine war in 2022, while countries with strong economies such as the United States actually experienced a recession. This research aims to discuss why the Indonesian economy remains stable amidst the global recession due to the Russian-Ukrainian war in 2022. The research method used in this research is a qualitative method with secondary data. Data validation in this research used the data source triangulation method with qualitative descriptive analysis. Based on the application of macroeconomic theory, the results of this research are that the Indonesian economy is stable against the global recession. Indonesia's strategy for maintaining its economy is by implementing expansionary fiscal policy, controlling interest rates through monetary policy, and supply side policies in the form of adjusting income tax rates, business support through capital loan interest rate subsidies, deregulation or cutting inefficient regulations.